PENERAPAN MEDIA BANDICAM BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS VIII MTS AL HIKMAH KLITIH - Khotimah, Khusnul; Putri, Febri Devita Lisgia; Satiti, Wisnu Siwi (Universitas KH. A. Wahab Hasbullah, 2021)
This study aimed to determine the differences in the problem solving abilities of students by applying learning with bandicam media based on problem based learning and conventional learning. This type of research was quantitative research. Quantitative Research was a scientific way to obtain data with a specific purpose or use in the form of numbers (scoring). The population in this study were all class VIII MTs Al-Hikmah Klitih. The sample in this study was class VIII MTs Al-Hikmah Klitih which consisted of two classes, namely class A and class B. The instruments used in this study were pre-test and post-test. Based on the results of the independent sample t test, a significant value of 0.002 <0.05 was obtained with a 95% confidence level, which means Ho was rejected and Ha was accepted. Thus, there was an effect of problem-based learning-based bandicam media to improve students' problem-solving abilities on student learning outcomes in class VIII MTs Al-Hikmah Klitih.